2014
DOI: 10.1080/09593330.2014.937464
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis-based endosulfan biotransformation: enrichment and isolation of endosulfan-degrading bacteria

Abstract: The study was conducted to isolate endosulfan biotransforming or biodegrading microbes based on chemotaxis. Pseudomonas aeruginosa strain KKc3, Ochrobactrum sp. strain KKc4, Achromobacter xylosoxidans strain KKc6 and Bacillus megaterium KKc7 were isolated based on their migration towards endosulfan in a soil column. Out of the four bacteria, B. megaterium converted endosulfan into toxic metabolite endosulfan sulphate, while the other three bacteria followed the non-toxic endosulfan diol pathway. The mixed cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition, plasmid conjugation machinery has been identified in Ochrobactrum plasmids ( 20 , 42 ), and horizontal gene transfer by conjugation was demonstrated in this genus ( 47 , 48 ). Ochrobactrum species was previously found to degrade a wide spectrum of recalcitrant and xenobiotic compounds, such as organophosphates ( 49 ), tetrachloroethene ( 50 ), dichloro-diphenyl-trichloroethane (DDT) ( 51 ), 2,4-dichlorophenoxyacetic acid, endosulfan ( 52 ) and aniline ( 53 ), among many others. Interestingly, ligninolytic activity was also reported from Ochrobactrum species ( 39 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, plasmid conjugation machinery has been identified in Ochrobactrum plasmids ( 20 , 42 ), and horizontal gene transfer by conjugation was demonstrated in this genus ( 47 , 48 ). Ochrobactrum species was previously found to degrade a wide spectrum of recalcitrant and xenobiotic compounds, such as organophosphates ( 49 ), tetrachloroethene ( 50 ), dichloro-diphenyl-trichloroethane (DDT) ( 51 ), 2,4-dichlorophenoxyacetic acid, endosulfan ( 52 ) and aniline ( 53 ), among many others. Interestingly, ligninolytic activity was also reported from Ochrobactrum species ( 39 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kumar and Pannu [ 83 ] identified Rhodanobacter lindaniclasticus, Alkaligens faecalis , and Pseudomonas aeruginosa as capable of dechlorinating lindane, Wang, et al [ 84 ] reported that Stroptomyces sp. strain can degrade DDT, and Seralathan, et al [ 85 ] confirmed that Pseudomonas aeruginosa, Ochrobacterium sp, and Achromobacter xylosoxidans degrade endosulfan and use it as a source of sulfur. These organochlorine pesticide-degrading species contain genes, e.g., lin and Esd genes that encode for dehalogenases, hydrolases, dehydrochlorinases, and monooxygenases enzymes that take part in mineralizing these compounds [ 86 ].…”
Section: Bioremediation Of Recalcitrant Organic Contaminantsmentioning
confidence: 99%
“…(Verma et al 2011), Achromobacter xylosoxidans, Bordetella sp. (Sand and Singh 2009), Klebsiella, Acinetobacter, Alcaligenes, Flavobacterium, Bacillus (Kafilzadeh et al 2015), and A. xylosoxidans (Seralathan et al 2015). Diagrammatic representation of endosulfan biodegradation by Pseudomonas mendocina ZAM1 strain is depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%